Online Shopping Habit atau Experience Memoderasi Customer’s Satisfaction, Trust, dan Learning Terhadap Online Repurchase Intention - Abigail Pasaribu; Lina Salim (Indonesia Marketing Association (IMA), 2022)
In covid-19 pandemi, online shopping is a very common form of activity. Various kinds of products are being sold online, which is one of them is book. Competition between booksellers is really tight. Therefore, sellers for many online bookstores found these days are not only people who specially sell books online, but well-known offline bookstores are also doing it. Satisfaction, trust, and learning are factors that influence customers’ desire to repurchase in order to maintain an online bookstore’s existence. Therefore, researcher investigate on effects of satisfaction, trust, and learning toward online repurchase intention with online shopping habit and experience as a moderator variable on thebook_holic online shop. Respondents for this research are 105 from 108 thebook_holic’s customers that had purchased (minimum) two times. The indicators used in this research had been tested and had been affirmed to have reliability value and good validity. The result of this research is that there are direct effects between satisfaction with outcome quality, satisfaction with process quality, learning and trust toward online repurchase intention. While online shopping habit and experience only moderate the relationship between satisfaction with outcome quality, satisfaction with process quality and online repurchase intention.